Encyclopedia of Life Sciences 2014
DOI: 10.1002/9780470015902.a0024941
|View full text |Cite
|
Sign up to set email alerts
|

Clustered Mutations in Human Cancer

Abstract: Mutations are the frequent cause of cancer. They are mostly viewed as independent events distributed ran domly across chromosomes. However, mutation dis tribution can be affected by permanent or transient features of genome structure and function. The extreme form of nonrandom distributions is a mutation cluster with multiple mutations concentrated in a tiny fraction of the genome. Multiple lesions in abnormally long regions of transient single-stranded deoxyribonucleic acid (DNA) can cause mutation clusters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Clustering ideas and techniques have been applied in cancer research in various incarnations and contexts aplenty -for a partial list of works at least to some extent related to our discussion here, see, e.g, [Chen et al, 2008a], [Chen et al, 2008b], [Kashuba et al, 2009], [Nik-Zainal et al, 2012], [Roberts et al, 2012], [Alexandrov et al, 2013a], [Alexandrov et al, 2013b], [Burns et al, 2013a], [Burns et al, 2013b], [Lawrence et al, 2013], [Long et al, 2013] [Roberts et al, 2013, [Taylor et al, 2013], [Xuan et al, 2013], [Alexandrov and Stratton, 2014], [Bacolla et al, 2014], [Bolli et al, 2014], [Caval et al, 2014], [Davis et al, 2014], [Helleday et al, 2014], [Nik-Zainal et al, 2014], [Poon et al, 2014], [Qian et al, 2014], [Roberts and Gordenin, 2014a], [Roberts and Gordenin, 2014b], [Roberts and Gordenin, 2014c], [Sima and Gilbert, 2014], [Chan and Gordenin, 2015], [Pettersen et al, 2015] and references therein. As mentioned above, even in NMF clustering is used at some (perhaps not-so-evident) layer.…”
Section: Discussionmentioning
confidence: 99%
“…Clustering ideas and techniques have been applied in cancer research in various incarnations and contexts aplenty -for a partial list of works at least to some extent related to our discussion here, see, e.g, [Chen et al, 2008a], [Chen et al, 2008b], [Kashuba et al, 2009], [Nik-Zainal et al, 2012], [Roberts et al, 2012], [Alexandrov et al, 2013a], [Alexandrov et al, 2013b], [Burns et al, 2013a], [Burns et al, 2013b], [Lawrence et al, 2013], [Long et al, 2013] [Roberts et al, 2013, [Taylor et al, 2013], [Xuan et al, 2013], [Alexandrov and Stratton, 2014], [Bacolla et al, 2014], [Bolli et al, 2014], [Caval et al, 2014], [Davis et al, 2014], [Helleday et al, 2014], [Nik-Zainal et al, 2014], [Poon et al, 2014], [Qian et al, 2014], [Roberts and Gordenin, 2014a], [Roberts and Gordenin, 2014b], [Roberts and Gordenin, 2014c], [Sima and Gilbert, 2014], [Chan and Gordenin, 2015], [Pettersen et al, 2015] and references therein. As mentioned above, even in NMF clustering is used at some (perhaps not-so-evident) layer.…”
Section: Discussionmentioning
confidence: 99%
“…Several prominent mutation signatures consisting of mutated nucleotide and immediate (1–2 nucleotides) surrounding context (reviewed in (5; 10; 53; 94; 106)) have been identified. Another striking pattern of mutagenesis revealed by genome-wide sequencing of multiple samples of several cancer types was the presence of many mutation clusters (up to several hundred per sample, see Table 1; also reviewed in (104; 105)), identified by two independent and complementary analytical methods. Using an approach based on statistical evaluation of cluster formation probability and on similarities with general clustering patterns identified in yeast studies (see below), our group (108) detected clustered mutagenesis in all three types of cancers (multiple myeloma, prostate and head-and-neck) whose genome mutation catalogues were available for analysis at the time (Figure 2).…”
Section: The Phenomenology Of Mutation Clusters In Cancersmentioning
confidence: 99%
“…An important biological consequence of non-uniform distribution of mutations is that a disproportionately large number of changes can accumulate in a limited section of a genome, forming a mutation cluster (Table 1). Crucially, such mutation clusters are abundant in human cancers (104; 105), afflictions which can be considered cases of highly accelerated evolution within somatic tissues. Recent studies have revealed various molecular mechanisms of clustered mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Proper chromatin organization has been demonstrated to have a striking effect on mutation rates, with rates being significantly higher in heterochromatin than in euchromatin (Roberts and Gordenin, 2014;Schuster-Bockler and Lehner, 2012). Therefore, heterochromatin aberrations in Nde1 À/À and Brap cKO neurons may be associated with heterochromatic DNA damage.…”
Section: Nde1 Lof Results In Heterochromatin Instability and Dsbs In ...mentioning
confidence: 99%